Wyobrażenia monet antycznych na okolicznościowych i obiegowych monetach z Ukrainy, Słowacji, Polski i Macedonii z lat 1993–2008. Formy, konteksty i znaczenie upamiętnień - Lajsner, Włodzimierz (Folia Praehistorica Posnaniensia, 2025)
The article deals with the depiction of ancient coins: Greek, Celtic, Roman and early Byzantine on contemporary circulation and commemorative coins issued in the years 1993–2008 by the central banks of Slavic countries, such as Ukraine, Slovakia, Poland and Macedonia. The coins mentioned are distinguished by a diverse cultural, historical and archaeological context, which is interpreted in terms of multiple connections with elements of ancient reality. The phenomenon of the reception of ancient coins is an example of building and strengthening one’s own national identity and conducting a historical policy by a given country.